Asymptomatic Summertime Shedding of Respiratory Viruses. (2nd January 2018) - Shaman, Jeffrey; Morita, Haruka; Birger, Ruthie; Boyle, Mary; Comito, Devon; Lane, Benjamin; Ligon, Chanel; Smith, Hannah; Desalle, Rob; Planet, Paul
Abstract : Sampling of visitors to a major New York City tourist attraction during April–July 2016 revealed substantial levels of asymptomatic and symptomatic respiratory virus shedding among the ambulatory adult population. Abstract: To determine rates of both symptomatic and asymptomatic infection among ambulatory adults, we collected nasopharyngeal swab specimens, demographic characteristics, and survey information from 1477 adult visitors to a New York City tourist attraction during April–July 2016. Multiplex polymerase chain reaction analysis was used to identify specimens positive for common respiratory viruses. A total of 7.2% of samples tested positive for respiratory viruses; among positive samples, 71.0% contained rhinovirus, and 21.5% contained coronavirus. Influenza virus, respiratory syncytial virus, and parainfluenza virus were also detected. Depending on symptomatologic definition, 57.7%–93.3% of positive samples were asymptomatic. These findings indicate that significant levels of asymptomatic respiratory viral shedding exist during summer among the ambulatory adult population.